2017
DOI: 10.1007/s11883-017-0694-6
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Evidence-Based Practices for Acute Stroke Care in Low- and Middle-Income Countries

Abstract: Major advances have been made during the past few decades in stroke prevention, treatment, and rehabilitation. These advances have been translated into practice in many high-income countries, but their uptake remains suboptimal in low- and middle-income countries. The review highlights the resources required to providing optimal acute stroke care in settings with limited resources. These resource levels were divided into minimal, essential, and advanced resources depending on the availability of stroke experti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
0
8
1
Order By: Relevance
“…[15] Moreover, it is reported that there are many hospitals that do not force HCPs to implement and follow evidence-based protocols regarding stroke management. [16] Continuing education (CE) and professional development could facilitate preparing competent and well-trained HCPs capable of recognizing and providing high-quality care to stroke patients. Therefore, the primary objective of this study is to evaluate the effectiveness of an evidence-based educational program on HCPs' knowledge of stroke, risk factors, warning signs, and proper course of diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Moreover, it is reported that there are many hospitals that do not force HCPs to implement and follow evidence-based protocols regarding stroke management. [16] Continuing education (CE) and professional development could facilitate preparing competent and well-trained HCPs capable of recognizing and providing high-quality care to stroke patients. Therefore, the primary objective of this study is to evaluate the effectiveness of an evidence-based educational program on HCPs' knowledge of stroke, risk factors, warning signs, and proper course of diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Ischemic strokes can be subdivided into thrombotic and embolic strokes [8]. It is emphasized that pharmacological actions aiming at limiting the area of damage should also include maintaining protective functions of neurons and endothelial cells of vessels composing neurovascular units [9]. Stroke management changed significantly what constitutes natural course of modern stroke units, better medical care, and more targeted motor and speech rehabilitation engaged in the early stage [10].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to general wards, these resource-intensive facilities have been associated with improved treatment outcomes in stroke patients in terms of mortality and dependency [10]. Though stroke units improve stroke outcomes both in HICs and LMICs, there are several barriers and only limited stroke units in LMICs [11][12][13].This coupled with the delay in hospital arrival, lack of stroke experts, shortage of medications, and cost could have potentially contributed to the poorer stroke treatment outcomes in LMICs when compared to HICs [2][3].…”
Section: Introductionmentioning
confidence: 99%